SOLID WASTE GENERATION AND RATE COMPONENTS PERCENTAGE IN BAGHDAD CITY - Fahem Chyad , Tasnim (Journal of Engineering and Sustainable Development, 2016)
A mixed methodological approaches including field investigation, questionnaire survey, and structured and face-to-face interviews were employed in the gathering of data to obtain Municipal Solid Waste (MSW) generation rate and physical compositions data. Samples were taken from different neighborhoods through a two sampling periods in 1/ 8 / 2015 to 1/ 9 / 2015 and in 1 / 12 / 2015 to 1 / 1 / 2016.Based on the results of the preliminary survey for 99% confidence interval and 5% standard error, the optimum size, n, was 100. A stratified random sampling procedure was applied, in which sampling sites were allocated to high, middle, and low-income socio-economic categories. The research concluded that the average generation rate of organic waste were 0.396 kg/capita. per day, cellulosic waste was 0.072 kg/ capita. per day, and total waste was 0.673 kg/per capita. per day.